Ordinary organizations? The German Football Association in the time of National Socialism - Rieck, Julian (Hispania Nova, 2020)
This article analyses the role of football –then one of the most popular sports– during the Nazi-dictatorship in Germany between 1933 and 1945. It does not only examine the history of the German Football Association (DFB) and here the process of Nazification (Gleichschaltung), but also about the development of the historiography undertaken in the last 20 years. These previous approaches have not been able to satisfactorily analyse the role of the DFB during National Socialism. Therefore, this article will make a proposal to address the issue differently and takes an approach into account that applies organizational sociology.